1987
DOI: 10.1002/hlca.19870700227
|View full text |Cite
|
Sign up to set email alerts
|

Copper and Silver Atoms in the β‐Cage of a Zeolite: Model Calculations

Abstract: The electronic structures ofthe 4-4 SBU, the 6-6 SBU, the8-cage, and the 8-cage with two 4-4 SBUs attached to it have been studied by means of EH-MO calculations. No indication of the formation of a band structure has been found. The HOMO region consists of many closely spaced, localized states, 98.6% of them concentrated on the 0-atoms. Reversible color changes of Cu+' and Ag" zeolites observed upon hydration-dehydration experiments can be understood as charge-transfer transitions from the HOMO concentrated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…After VIR, the intensity of band around 800 nm declines slightly. This is caused by the incomplete reduction of Cu(II) and oxygen-to-metal charge transfer of Cu(I) in the 6-6 secondary building unit of zeolite 41 . Meanwhile, two new absorption peaks at 350 and 450 nm readily attributed to the charge transfer transitions (3d 10 → 3d 9 4s 1 ) of Cu(I) in the zeolite matrix can be clearly identified, which is absent in Cu(II)Y 42,43 .…”
Section: Resultsmentioning
confidence: 99%
“…After VIR, the intensity of band around 800 nm declines slightly. This is caused by the incomplete reduction of Cu(II) and oxygen-to-metal charge transfer of Cu(I) in the 6-6 secondary building unit of zeolite 41 . Meanwhile, two new absorption peaks at 350 and 450 nm readily attributed to the charge transfer transitions (3d 10 → 3d 9 4s 1 ) of Cu(I) in the zeolite matrix can be clearly identified, which is absent in Cu(II)Y 42,43 .…”
Section: Resultsmentioning
confidence: 99%
“…An extended Hiickel quantum-chemical calculation showed that the color change correlated with charge transfer from framework oxygens to silver cations; the lowest energy transition in Ag-A was a charge transfer from an orbital localized mainly on framework oxygens to that of a silver ion in a 6-ring. 40 After nearly all of the water is lost, further changes in color must be attributed to the increasing extent of Ag+ reduction (to the formation of silver clusters). The shortest Ag-0 bonds and the darkest colors occur when little or no water is retained and little or no Ag+ has been reduced.…”
Section: Silver Clusters In Completely Ag+ -Exchanged Zeolite a (Ag-a)mentioning
confidence: 99%
“…Some aspects of the optical spectrum of Cu+ zeolites have previously been reported.3 MO studies, however, suggest a different interpretation, notably that the first electronic transition is due to a Cu+ t zeolite-oxygen lone-pair LMCT transition. 4 Samples with different Cu2+ exchange levels were prepared by ion exchange at room temperature for 3 h with aqueous solutions containing the desired amount of Cu2+ as Cu(NO&. As starting materials Na-4A (Bayer AG: Baylit T) and Na-13X (Union Carbide) were used.…”
Section: Luminescence Experiments On Copper(1) Zeolitesmentioning
confidence: 99%